Exploring the experiences and needs of homeless aboriginal and torres strait islander peoples with neurocognitive disability. Issue 2 (5th July 2019) - Townsend, Clare; McIntyre, Michelle; Wright, Courtney J.; Lakhani, Ali; White, Paul; Cullen, Jennifer
Abstract: Objective: The current study explored the experiences and aspirations of a cohort of Aboriginal and Torres Strait Islander adults with neurocognitive disability residing in a homeless shelter in regional Queensland, Australia. Neurocognitive disability (NCD) refers to any acquired disorder or injury to the brain where the primary clinical deficit is in cognitive function. Method: The data reported on in this paper emerged from a broader study that aimed to understand the extent and nature of neurocognitive disability amongst homeless Aboriginal and Torres Strait Islander people. The broader study found high levels of NCD which impacted on people's ability to participate in society. As part of the study, qualitative information was sought regarding participant life experiences. A culturally safe and acceptable structure of "past, present and future" was applied to open-ended questions. Results: Thematic analysis of the data identified four broad themes of i) normalisation of illness and disability; ii) trauma and loss; iii) socioeconomic disadvantage; and iv) hope and disempowerment. This paper reports on these themes and experiences, which occurred across the life span, intersected with NCD, and contributed to what we have termed 'complex disablement' amongst this cohort. Conclusions: While causal links between life experience, disability and disablement are not always clear, our findings suggest that attempts to address homelessness must engage with this complexity. The application of holistic, intersectoral supports, which encompass culturally informed, community driven approaches are needed. Understanding the impacts of individual and intergenerational trauma is crucial to safe and effective service provision for this cohort.